The activation of endothelin-1 pathway during methionine-induced homocysteinemia mediates endothelial dysfunction in hypertensive individuals. - Tousoulis, D; Bouras, G; Antoniades, C; Marinou, K; Miliou, A; Papageorgiou, N; Chatzis, G; Tentolouris, C; Tsioufis, C; Stefanadis, C (2010)
OBJECTIVES: Endothelin-1 (ET-1) is a key regulator of arterial blood pressure in humans, and homocysteinemia is associated with increased oxidative stress. It is still unclear whether homocysteine-induced oxidative stress is implicated in the regulation of ET-1 expression. We examined the impact of acute homocysteinemia on endothelial function in hypertensive patients and healthy individuals, and the potential role of ET-1. METHODS: In this double-blind, placebo-controlled study, 39 hypertensive and 49 healthy individuals were randomized to receive high-dose vitamins (2 g vitamin C and 800IU vitamin E) or placebo followed by methionine loading 100 mg/kg body weight. Endothelium-dependent dilation (EDD) and endothelium-independent dilation (EID) of the brachial artery were evaluated by plethysmography, at baseline and 4 h postloading (4 h PML). ET-1 was measured by ELISA, whereas total lipid hydroperoxides (per-ox) levels were measured by a commercially available photometric technique. RESULTS: Acute, methionine-induced homocysteinemia decreased EDD in all study groups (P < 0.001 for all), whereas vitamins pretreatment failed to prevent this effect, despite the vitamins-induced reduction of peroxidation in the hypertensives group (P < 0.05). On the contrary, methionine loading significantly increased plasma ET-1 levels only in hypertensives (P < 0.05), an effect which was not prevented by antioxidant vitamins (P < 0.05). EID remained unchanged after methionine loading, in all study groups (P = NS for all groups). CONCLUSION: Experimental homocysteinemia rapidly blunts endothelial function in both hypertensive individuals and healthy individuals. The rapid elevation of ET-1 levels observed only in hypertensives, suggests that ET-1 may be the key mediator of homocysteine-induced endothelial dysfunction, independently of oxidative stress.